183k views
0 votes
If f(x) = 3^x+10x and g(x) = 4x-2, find (f-g)(x)

2 Answers

3 votes
(f-g)(x) = f(x) - g(x) = 3^x + 10x - (4x - 2)  = 3^x + 6x + 2 Answer
User Bvoyelr
by
6.9k points
7 votes

Answer:

(f-g)(x) is
3^(x)+6x+2

Explanation:

The provided expression is
f(x)=3^(x)+10x and
g(x)=4x-2

To find (f-g)(x), subtract function g(x) from function f(x)


(f-g)(x)


(3^(x)+10x)-(4x-2)

Combine the like terms first,


3^(x)+10x-4x+2


3^(x)+6x+2

Hence, (f-g)(x) is
3^(x)+6x+2

User Justin Lin
by
5.9k points